Unfair Contract Terms in the Perspective of Civil Law and Consumer Protection in Indonesia - Josef Purwadi Setiodjati; Anggo Doyoharjo; Dora Kusumastuti (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This article aims to analyze the regulation of unfair contract terms from the perspective of civil law and to examine the issues and efforts to strengthen consumer protection in Indonesia. The main issue raised is how the legal construction of unfair clauses in standard contracts and the extent of regulatory effectiveness in protecting consumers from bargaining position imbalances. This research uses a normative juridical method with a legislative and conceptual approach, thru the analysis of the Civil Code, Law Number 8 of 1999 on Consumer Protection, as well as related regulations such as the Electronic Information and Transactions Law and the Personal Data Protection Law. The research results show that although Indonesian positive law has imposed restrictions on standard clauses that harm consumers, particularly thru Article 18 of the Consumer Protection Law, the practice of unfair contract terms still prevails due to weak law enforcement, low consumer literacy, and the dominance of business actors in contract drafting. Therefore, it is necessary to strengthen consumer protection thru regulatory harmonization, increased effectiveness of supervision and law enforcement, as well as the development of transparent and fair contracts. Thus, consumer protection is not only formal but also capable of ensuring substantive justice in contractual relationships